TOTAL QUALITY MANAGEMENT DAN PARTISIPASI ANGGARAN SEBAGAI ANTISEDEN KINERJA MANAJERIAL DI PABRIK GULA KOTA MALANG - Annisa Fatimah; Agnes Kristina Pardede; Anik Kusmintarti (Universitas Gajayana Malang, 2020)
Total quality management (TQM) and budget participation become a significant step for the company to achieve optimal employee performance. For this reason, this study is intended to add empirical evidence related to the relationship of these variables. 39 respondents were selected to this research through questionnaires distribution to all employees who involved in budget participation on company which apply the TQM concept at the Sugar Factory of Malang. Multiple linear regression analysis with Partial Least Square (PLS) is used to analyze. The analysis results prove that TQM and budgetary participation have a significant effect on employee performance.